2020
DOI: 10.1017/hpl.2020.44
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on high photon flux nonclassical light and applications in nonlinear optics

Abstract: Nonclassical light sources have a vital role in quantum optics as they offer a unique resource for studies in quantum technology. However, their applicability is restricted by their low intensity, while the development of new schemes producing intense nonclassical light is a challenging task. In this perspective article, we discuss potential schemes that could be used towards the development of high photon flux nonclassical light sources and their future prospects in nonlinear optics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Early one-dimensional numerical simulations [40] predicted that using~5 fs IR laser pulses with intensity on target in the range of I L~1 0 20 W/cm 2 , high harmonics in the photon energy range of~60 eV can be generated with conversion efficiency in the range of 10 −1 -10 −2 , while the generation of harmonics in the keV photon energy range can take place with conversion efficiency in the range of~10 −4 . More recent two-dimensional numerical simulations [29,[41][42][43] for I L~1 0 19 W/cm 2 predict typically two orders of magnitude lower efficiencies, in agreement with experiments [42][43][44], i.e.,~10 −4 in the range of 30-70 eV.…”
Section: Quantum Spectrometry In Laser-plasma Interactionssupporting
confidence: 84%
See 1 more Smart Citation
“…Early one-dimensional numerical simulations [40] predicted that using~5 fs IR laser pulses with intensity on target in the range of I L~1 0 20 W/cm 2 , high harmonics in the photon energy range of~60 eV can be generated with conversion efficiency in the range of 10 −1 -10 −2 , while the generation of harmonics in the keV photon energy range can take place with conversion efficiency in the range of~10 −4 . More recent two-dimensional numerical simulations [29,[41][42][43] for I L~1 0 19 W/cm 2 predict typically two orders of magnitude lower efficiencies, in agreement with experiments [42][43][44], i.e.,~10 −4 in the range of 30-70 eV.…”
Section: Quantum Spectrometry In Laser-plasma Interactionssupporting
confidence: 84%
“…In QO, the quantum description of a classically oscillating electromagnetic field [2,3] opened the way for fascinating investigations in quantum technology [11][12][13][14]. Central to these studies are non-classical light sources [11,[15][16][17][18][19] as they offer a unique resource for quantum communication, information and computation, as well as atomic physics, visual science, and high precision interferometry applied for the detection of gravitational waves, to name a few [11][12][13][14]. On the other hand, in SLFP, the development of high-power femtosecond (fs) pulsed laser sources [4,5,11] and of the classical and semi-classical description of intense laser-matter interaction [6][7][8][9][10][11][20][21][22] opened the way for studies ranging from relativistic electron acceleration [23,24], and high-order harmonic generation (HHG), to attosecond science and ultrafast optoelectronics [6][7][8][9][10][11]25].…”
Section: Introductionmentioning
confidence: 99%
“…The derivation of the transition probability per unit time for N-photon ionization when all real bound atomic intermediate states are assumed sufficiently far from resonance [31][32][33][34] indicates that the rate of the process is proportional to an effective N-photon matrix element multiplied by the Nth-order intensity correlation function [15,16]. In view of the dependence of the correlation functions on the stochastic properties of the radiation, the rate of such a process can be affected dramatically by the intensity fluctuations of the source [35]. As a prototype example, one can take an 11-photon ionization process induced by thermal radiation whose Nth order intensity correlation function is given by N!…”
Section: Introductionmentioning
confidence: 99%
“…The reference [19] showed that the bunching property of the light field can be modified via modulation of the intensity fluctuation. In the presence of the fluctuating light pump, the multiphoton absorption [20,21], multiphoton ionization [22,23], generation of optical harmonics [17,24], and modulation instability [25] were hugely enhanced. Therefore, stronger light intensity fluctuation plays an important role in many optical applications.…”
Section: Introductionmentioning
confidence: 99%